Les reflets fragmentés de la traduction contemporaine : quels changements ? Quelles entraves ? Quelles modalités ? Quels enjeux ? - Lécrivain, Claudine (Verbum – Analecta Neolatina, 2013)
The present article discusses the emerging future of the field of translation. It focuses on the impact of new technologies, new figures of the translator, the notion of the author, the reader and the space for the source text in some translation processes in order to help us confront the limitations of the traditional concept of translation.